2022
DOI: 10.1186/s12944-021-01617-3
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific contribution of lipid accumulation product and cardiometabolic index in the identification of nonalcoholic fatty liver disease among Chinese adults

Abstract: Background Lipid accumulation product (LAP) and cardiometabolic index (CMI) are two novel obesity-related indexes associated with enhancing metabolic disease (MD) risk. Current evidences suggest that the differences in sex hormones and regional fat distribution in both sexes are directly correlated with MD and nonalcoholic fatty liver disease (NAFLD) risk. Hence, NAFLD incidences reflect sex differences. Herein, we examined the accuracy of LAP and CMI in diagnosing NAFLD in both sexes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…In a cross-sectional study involving 40,459 participants from southern China, LAP showed a strong association with the diagnosis and severity of NAFLD ( 31 ), in line with findings from northern China ( 11 ). Besides, LAP is one of the few indicators that can reflect sex differences in FLD, which is calculated for males and females respectively.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In a cross-sectional study involving 40,459 participants from southern China, LAP showed a strong association with the diagnosis and severity of NAFLD ( 31 ), in line with findings from northern China ( 11 ). Besides, LAP is one of the few indicators that can reflect sex differences in FLD, which is calculated for males and females respectively.…”
Section: Discussionsupporting
confidence: 78%
“…Besides, atherogenic index of plasma (AIP) was considered as a regular monitoring index of NAFLD for obese men due to its strong correlation with NAFLD in obese participants ( 9 ). However, most researchers only aimed at one or two parameters without comparison among more indexes ( 10 , 11 ). The latest consensus suggests that there are three subgroups in the diagnosis of MAFLD, including Obesity, Lean, and T 2 DM MAFLD subgroups ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The data from the Third National Health and Nutrition Examination Survey conducted in the United States demonstrated that LAP, which combined abdominal adiposity and circulating TG concentration, was much superior for predicting diabetes than BMI [ 14 ]. Recently, several studies found LAP could be used as an effective predictor of IR and NAFLD, and what's more, it had a relatively higher predictive value than traditionally applied surrogate indices [ 6 , 18 , 20 ]. VAI deriving from a formula based on anthropometric and biochemical parameters could indirectly express visceral adipose function and was a useful marker for evaluating IR in clinical practice [ 15 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Simple, cost-effective, and non-invasive tests for NAFLD are preferred over liver biopsy, and LAP is a valid alternative [ 43 ]. LAP performs better than BMI as a marker for NAFLD and is also a risk factor for diabetes [ 44 ], metabolic syndrome [ 45 , 46 ], and cardiovascular diseases [ 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the TyG index is a novel marker with high specificity and sensitivity in diagnosing metabolic syndrome [ 49 ]. Additionally, the best-validated steatosis biomarker-related index is the FLI, which is also helpful for evaluating NAFLD, with a high correlation with imaging and histological findings [ 43 ], as well as being beneficial for assessing CVD, since the risk factors are the same for both [ 43 ]. Furthermore, adipose tissue-related indicators have been correlated with higher morbidity and mortality rate among patients with NAFLD [ 27 , 30 ].…”
Section: Methodsmentioning
confidence: 99%